Rights of muslim women after divorce in Malaysia and related issues / Farahdilah Ghazali…[et al.] - Ghazali, Farahdilah; Jaaffar, Haryani; Abd Azis, Hawa Darlida; Syed Anuar, Sharifah Lina Hafizah; Harun, Ummi Sharmimi (2010)
This research paper examines the current law on Islamic Family Law governing the rights of Muslim women after divorce, its enforcement and the related issues as applicable in Malaysia. As Islamic Law is expected to contribute to the efficacy and adequacy of the law of the right of women, this study is based on library researches and interviews. The researches analyse the rights of Muslim women after divorce in two categories which are financial and non - financial rights. For financial rights, the rights are nafkah, mahr/maskahwin, mut'ah and harta sepencarian while the later type is the right for hadhanah which determined in the main statute, Islamic Family Law Act (Federal Territory) 1984 and other State Enactments. This study also includes the problems on enforcement with regards to the non - compliance of the court order and the related issues on the Syariah Court system which consist of the issue of delayed cases. The study clarifies on the rights available for Muslim women after divorce not only with reference to the relevant statutes but also from the expert's opinion. The current laws which were provided by the authorities not clear enough as to the certain controversial issues on the rights of the Muslim women and the study will look at the court's approach based on the decided cases. The study also reveals on the problems of delayed cases occurred in Syariah Court and comes with the solutions and recommendations for this difficulty. The ambiguity on certain matters as to the rights of women after divorce proved that there are loopholes {lacuna) in our Islamic Family Law and opportunity to improve this law.